2020
DOI: 10.1101/2020.05.22.109017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of NR4A Ligands that Directly Bind and Modulate the Orphan Nuclear Receptor Nurr1

Abstract: Nurr1/NR4A2 is an orphan nuclear receptor transcription factor implicated as a potential drug target for neurological disorders including Alzheimer’s and Parkinson’s diseases. Previous studies identified small molecule modulators of NR4A nuclear receptors including Nurr1 and Nur77/NR4A1; it remains unclear whether these ligands affect Nurr1 through direct binding or indirect non-binding mechanisms. We assessed a panel of twelve ligands reported to affect NR4A activity for Nurr1-dependent and Nurr1-independent … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…As an example, it has been demonstrated that the GR can act as a transcriptional regulator of NURR1, suggesting that glucocorticoids might be used to regulate NURR1 expression [ 87 ]. At present, a significant number of research projects aimed at identifying new NURR1 ligands for drug development are underway [ 141 , 142 , 143 ].…”
Section: Nurr1: An Early Biomarker and Novel Target For Preventionmentioning
confidence: 99%
“…As an example, it has been demonstrated that the GR can act as a transcriptional regulator of NURR1, suggesting that glucocorticoids might be used to regulate NURR1 expression [ 87 ]. At present, a significant number of research projects aimed at identifying new NURR1 ligands for drug development are underway [ 141 , 142 , 143 ].…”
Section: Nurr1: An Early Biomarker and Novel Target For Preventionmentioning
confidence: 99%